Experimental and numerical performance analysis of a converging channel heat exchanger for PV cooling. (October 2015) - Baloch, Ahmer A.B.; Bahaidarah, Haitham M.S.; Gandhidasan, Palanichamy; Al-Sulaiman, Fahad A.
Graphical abstract: Highlights: Effect of varying converging angle on temperature characteristics of PV surface studied. Optical, CFD, thermal, and electrical models developed for the analysis. Experimental measurements carried out for two configurations for June and December. Using this cooling technique, maximum cell temperature reduction was 57.8%. Maximum percentage improvement in power output was 35.5%. Abstract: An experimental and numerical investigation of a cooling technique called as converging channel cooling intended to achieve low and uniform temperature on the surface of PV panel is presented in this paper. Experimental evaluation for an uncooled PV system and a converging channel cooled PV system was carried out subjected to the hot climate of Saudi Arabia for the month of June and December. Detailed modeling was performed using numerical analysis to investigate the effect of changing the converging angle on the thermal characteristics of the PV system. Based on the developed model, two degrees angle showed the best performance in terms of temperature distribution and average cell temperature with a standard deviation of 0.91 °C. A comprehensive system model was developed to assess the performance of PV systems numerically by coupling the optical, radiation, thermal, computational fluid dynamics, and electrical model. Thermal measurements for an uncooled PV showed cell temperature as high as 71.2 °C and 48.3 °C for the month of June and December, respectively. By employing converging cooling, cell temperature was reduced significantly to 45.1 °C for June and to 36.4 °C for December. Maximum percentage improvement in power output was 35.5% whereas maximum percentage increase in the conversion efficiency was 36.1% when compared to the performance of an uncooled PV system. For cost feasibility of an uncooled and cooled PV system, levelized cost of energy (LCE) analysis was performed using the annual energy yield simulation for both systems. LCE was found to be 1.95(€/kW h) for an uncooled PV system which was reduced to 1.57(€/kW h) for converging cooled PV system with a relative percentage decrease of 19.5%, hence making it economically viable.